Cards Against Humanity - International Edition : A party game for horrible people (2017)
Cards Against Humanity is a party game for horrible people. Each round one player asks a question from a black card, everyone else answers with their funniest white card. Players: 4 to 20+ Duration of the game: 30 to 90 minutes.
Cards Against Humanity is een gezelschapsspel voor vreselijke mensen. Elke ronde stelt een speler een vraag van een zwarte kaart, alle anderen antwoorden met hun grappigste witte kaart. Spelers: 4 tot 20+ Duur van het spel: 30 tot 90 minuten.
Keywords: Gezelschapsspellen; Party Games